Monetary policy with a state-dependent inflation target in a behavioral two-country monetary union model - Christian Proa\~no Acosta; Benjamin Lojak (Bamberg University, Bamberg Economic Research Group (BERG), 2020)
In this paper we study the implementation of a state-dependent inflation target in a two-country monetary union model characterized by boundedly rational agents. In particular, we use the spread between the actual policy rate (which is constrained by the zero-lower-bound) and the Taylor rate (which can become negative) as a measure for the degree of ineffectiveness of conventional monetary policy as a stabilizing mechanism. The perception of macroeconomic risk by the agents is assumed to vary according to this measure by means of the Brock-Hommes switching mechanism. Our numerical simulations indicate a) that a state-dependent inflation target may lead to a better macroeconomic and inflation stabilization, and b) the perceived risk-sharing among the monetary union members influences the financing conditions of the member economies of the monetary union.
Keywords: E52; E7; F02; 330; Monetary Policy; Monetary Unions; Zero Lower Bound; Inflation Targets; Behavioral Macroeconomics